1998
DOI: 10.1063/1.122398
|View full text |Cite
|
Sign up to set email alerts
|

Interlayer exchange in (Ga,Mn)As/(Al,Ga)As/(Ga,Mn)As semiconducting ferromagnet/nonmagnet/ferromagnet trilayer structures

Abstract: Magnetic properties of all-semiconductor (Ga,Mn)As/(Al,Ga)As/(Ga,Mn)As trilayer structures are studied. The interactions between the two ferromagnetic (Ga,Mn)As layers are investigated by magnetotransport measurements in a number of samples with different GaAs thickness or with different Al content in the intermediary nonmagnetic (Al,Ga)As layer. The results indicate that carriers present in the nonmagnetic layer mediate the coupling between the two ferromagnetic layers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 9 publications
0
37
0
Order By: Relevance
“…The experiments were performed as a function of nonmagnetic layer thickness, to study the distance dependence of the coupling. It was found that the coupling between the magnetic layers is FM and strongly depends on the barrier height [81]. It was then suggested that the inter layer coupling is induced by the holes in GaAIAs.…”
Section: Other Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiments were performed as a function of nonmagnetic layer thickness, to study the distance dependence of the coupling. It was found that the coupling between the magnetic layers is FM and strongly depends on the barrier height [81]. It was then suggested that the inter layer coupling is induced by the holes in GaAIAs.…”
Section: Other Issuesmentioning
confidence: 99%
“…The coupling between magnetic GaMnAs layers was investigated for a series of trilayer system, consisting of GaMnAs layers separated by nonmagnetic GaAlAs layer [81]. The experiments were performed as a function of nonmagnetic layer thickness, to study the distance dependence of the coupling.…”
Section: Other Issuesmentioning
confidence: 99%
“…In contrast, in the (Ga,Mn)As-based semiconductor ferromagnetic/ nonmagnetic systems interlayer coupling of opposite FM sign was observedby magnetic measurements [13][14][15], neutron diffraction [16], and polarized neutron reflectometry [17]. These structures differ from the previously considered EuS-based ferromagnetic semiconductor multilayers by many aspects, which all can affect the IEC.…”
Section: Interlayer Coupling and The Tight-binding Modelmentioning
confidence: 61%
“…This so-called tunnel anisotropic magnetoresistance (TAMR) effect was observed when the saturation magnetization direction was changed in-plane [9][10][11] as well as when it was turned perpendicular to the magnetic layer [11,12]. It was also shown that the magnetization vectors of consecutive (Ga,Mn)As ferromagnetic layers separated by nonmagnetic spacers in a multilayer structure are correlated by an interlayer coupling [13][14][15][16][17] and structures exhibiting giant magnetoresistance (GMR) were obtained [14].…”
Section: Introductionmentioning
confidence: 89%
“…In the latter case one should use asymmetric trilayer structures (see Fig. 1b) to allow for the clear distinction between the non-coupled layers due to their different coercive fields (the method used, e.g., in the studies of GaMnAs-AlGaAs trilayers [33]). …”
Section: Interlayer Exchange In Ferromagnetic Semiconductor Superlattmentioning
confidence: 99%